KRITIK SOSIAL DALAM LIRIK LAGU DURMAGATI DADI MENTRI KARYA KAJAWI: ANALISIS WACANA KRITIS VAN DIJK - Suwono; Hari Windu Asrini (STKIP Subang, 2026)
This study aims to examine the construction of social criticism discourse in the song lyrics